2020
DOI: 10.1186/s12957-020-01978-6
|View full text |Cite
|
Sign up to set email alerts
|

Nadir CA-125 serum levels during neoadjuvant chemotherapy and no residual tumor at interval debulking surgery predict prognosis in advanced stage ovarian cancer

Abstract: Background: Recent phase III randomized trials have suggested that neoadjuvant chemotherapy followed by interval debulking surgery (NACT-IDS) is a treatment option for patients with advanced epithelial ovarian cancer. This study aimed to use CA-125 and computed tomography (CT) scanning to generate a simple and clinically applicable model of predicting complete cytoreduction by interval debulking surgery (IDS) and the overall survival in patients who receive taxane/platinum-based chemotherapy as neoadjuvant che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The QUIPS quality assessment outcomes of the included studies are reported in Supporting Information Supplementary Table S3 . Generally, the risk of bias was low for most studies [ 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The risk of bias was moderate for only three studies [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The QUIPS quality assessment outcomes of the included studies are reported in Supporting Information Supplementary Table S3 . Generally, the risk of bias was low for most studies [ 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The risk of bias was moderate for only three studies [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were prospective cohort studies [ 15 , 25 ]; the other twelve studies were retrospective cohort studies [ 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 ]. Four out of 14 studies reported the results of patients who underwent primary CRS [ 15 , 16 , 17 , 25 ], and nine studies reported the results of patients who underwent interval CRS [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 ]. One study reported patients undergoing either primary or interval CRS [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary treatment consists of optimal primary cytoreductive surgery followed by systemic chemotherapy. In patients unsuitable for primary cytoreductive surgery due to advanced age, frailty, poor performance status, comorbidities, or disease that is unlikely to be optimally cytoreduced, neoadjuvant chemotherapy (NACT) followed by interval cytoreductive surgery should be considered [ 2 , 3 ]. Therefore, cytoreductive surgery after NACT is often undertaken in patients who are physically, nutritionally, and/or psychologically affected.…”
Section: Introductionmentioning
confidence: 99%